La relación docente-alumno y su influencia en el clima escolar de los niños de la escuela de educación básica unidocente profesora Clorinda Espinosa, parroquia Chantaco 2020-2021 - Orosco Cuenca, Jessica Paulina (2022)
The research work entitled, THE TEACHER-STUDENT RELATIONSHIP AND ITS INFLUENCE ON THE SCHOOL CLIMATE OF THE CHILDREN OF THE BASIC EDUCATION SCHOOL UNIDOCENTE PROFESORA CLORINDA ESPINOSA, CHANTACO PARISH 2020-2021, In this research was carried out through a quantitative approach; of descriptive type; of non-experimental design and cross-sectional - correlational, the scale of school climate according to Moos and Trickett applied to the population of ten children was used; From the results it was evidenced that 40% of the students have difficulties in interaction and companionship, in the same way the scale of student perception was used by the teacher of García - Bacete applied to the teacher of the institution from which it was obtained as a result that 80% of the students present difficulties with respect to communication or friendship ties. It is concluded that those evaluated present difficulties in aspects of interaction, companionship, cooperation and communication. In view of these results, it is recommended to apply the psycho-educational proposal designed in this research, which is based on the training of assertive communication techniques, to strengthen the teacher-student relationship and improve the school climate of the students of the school. Key words: student, school climate, teacher, communication, single-teacher school.